The use of crumb rubber in asphalt mixtures using the dry process - Neto, Silvrano Adonias Dantas (2005)
The modification process of hot mix asphalts in which crumb rubber is initially mixed with the mineral aggregates before the addition of the binder is known as dry process. This process has as main advantages the use of conventional mixing plants and, at least in principle, has no limitation of the incorporated rubber content. The aim of this paper is to study the influence of the incorporated crumb rubber content in the mechanical behavior of dense graded mixes ( grade envelope C of Brazilian specification DNER-ES 313/97). For this purpose, laboratory tests were carried out to determine the main properties to be used in numerical analyses of a structure of flexible pavement executed with that type of asphalt mixture. The mechanical properties of asphalt hot mixes used in the numerical analysis were determined by laboratory tests (stiffness modulus and fatigue life). The studied asphalt hot mixes were produced with a crumb rubber obtained by the milling process at ambient temperature and a straight binder AC 50/70 (classification by penetration). The incorporated rubber content varied from 2% up to 3,6% in relation to the mineral aggregate mixture. For the sake of comparison, a conventional asphalt mixture produced with straight binder AC 50/70 and an asphalt-rubber hot mix produced by wet process were also studied. The results showed that the asphalt hot mixes modified with crumb rubber by dry process presented a significant improvement in terms of mechanical behavior in relation to conventional asphalt hot mixes, especially in terms of increase of fatigue life, as can be observed in the numerical analysis performed.